Financial dollarization in emerging markets: an insurance arrangement - Husnu C. Dalgic (International Economic Review, 2024)
Households in emerging markets hold significant amounts of dollar deposits whereas firms have significant amount of dollar debt. Motivated by perceived dangers, policymakers consider regulations to limit dollarization. I draw attention to an important benefit of dollarization: it serves as an insurance arrangement in which firms provide income insurance. Emerging market exchange rates tend to depreciate in recessions so that households prefer holding deposits denominated in dollars. They effectively starve local financial markets of local currency; raising local interest rates over USD rates and causing entrepreneurs to borrow in dollars. This premium is the price paid by households for~insurance.
Keywords: 330